Factors Related To Health Insurance BPJS PBI Ownership Among Household Members - Yosalli Yosalli; Heni Rusmitasari; Suyitno Suyitno; Sariana Sariana; Maretalinia Maretalinia (Sean Institute, 2023)
This study aims to examine factors related to household members having BPJS PBI health insurance in Indonesia. A multistage cluster sample design was used to describe a probability sample of households and eligible females. The data were collected from the IPUMS PMA 2020 in Indonesia data. Based on chi-square analysis shows that the wealth quintile; middle, and poor, and residence; rural have a high association with ownership of BPJS PBI in Indonesia, while sex of a household member, age group, marital status, wealth quintile, and residence do not have significant association. The results of this study show that people who are poor and have a moderate level of wealth, stay in the rural, as children in the household, and live in marital status affect the ownership of BPJS PBI. These results can be used to formulate a strategy for strengthening health insurance ownership.